Bowel Preparations for Colonoscopy: Current Medical Practices in Pakistani Hospital Settings - Samina Naz, Bushra Tasneem, Hassaan Hanif Khan, Asma Kafeel, Muhammad Abid Owais, Aisha Tasneem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the quality of bowel preparations concerning the Boston Bowel Preparation Score (BBPS) and to analyze the administration, ease, palatability, and side effects of practices. Study design: Cross-sectional study Place and Duration: this study was conducted in Liaquat University of Medical and Health Sciences Jamshoro from October 2021 to March 2022 Methodology: The present study incorporated 132 patients who visited the hospital for a colonoscopy. Patients above 18 years of age were included, whereas patients with surgical procedures were excluded from the study. Participants were evaluated through pre-designed proforma for demography, dietary recommendations, side effects, procedure indications, bowel preparations, and patient ease of the bowel preparations. BBPS was used to access the bowel preparation. A score ≥ 5 was regarded as satisfactory. Results: Out of 132 patients, 73 (55.3%) were males. Seventy-one (53.8%) patients received Polyethylene glycol-based bowl preparation, and sixty-one (46.2%) patients received sodium phosphate-based preparation. Chronic constipation was the most typical cause of colonoscopy. Common side effects were vomiting (12.1%), nausea (1.5%), and bloating (3%). More than half of them responded that the preparations were palatable. A satisfaction rate of 80.3% was observed in patients with both preparations. BBPS of above five was observed in 109 (82.6%) patients. Conclusion: Polyethylene glycol and sodium phosphate preparations have been widely used in clinical practices for cleansing the colon. Sodium phosphate-based preparation was found more effective. Keywords: Bowel cleansing agents, Colonoscopy, Endoscopy, Polyethylene Glycol, Sodium phosphate.